Sport Event as a Driver of Mass Sport Development - E. A. Gureeva (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
Russia has gained large experience in arranging sport events of different scale. Big sport competitions of international level were held, such summer Universiade ‘Kazan-2013’ and winter Universiade in Krasnoyarsk in 2019, a number of world championships and biggest mega-sport events: the 22nd Olympic Games and 11th Paralympics in Sochi and Football World Cup FIFA ‘Russia-2018’. Changes in the country have cut the possibility of arranging sport events of this level on the territory of the Russian Federation. It is necessary to mention that many sport events, such as Super Bowl, NHL and NBA competitions that show the maximum viewings and profits are national championships. On the background of big sport problems, a rise in the number of international events of mass sport is evident, they are mainly organized by private initiatives. Data of VCIOM sociological research and statistic information presented a profile of potential participant of mass sport events. It is a man at the age of 37, who prefers endurance competitions. Such sports as steeplechase, running, triathlon, swimming and ski race are the most popular in this segment of competitions. Apart from strategic goals, sport events have a certain economic potential. The potential economic capacity of 4-days competition with the average number of participants and accompanying people makes up 16.2 m euros or 1.766 B rubles. The article studies several organizational-economic models typical of different sectors of sport competitions. The author shows that potential economic effect of big sport events is much higher, however, this effect is not always attained in full. For competitions of mass sport social effect is more typical.